Androgen-mediated maternal effects and trade-offs: postnatal hormone development, growth, and survivorship in wild meerkats - Davies, Charli S.; Shearer, Caroline L.; Greene, Lydia K.; Mitchell, Jessica; Walsh, Debbie; Goerlich, Vivian C.; Clutton-Brock, Tim H.; Drea, Christine M. (Frontiers in Endocrinology, 2024)
Mammalian reproductive and somatic development is regulated by steroid hormones, growth hormone (GH), and insulin-like growth factor-1 (IGF-1). Based largely on information from humans, model organisms, and domesticated animals, testosterone (T) and the GH/IGF-1 system activate sexually differentiated development, promoting male-biased growth, often at a cost to health and survivorship. Augmented prenatal androgen exposure in females may produce similar developmental patterns and trade-offs. We examine maternal effects in wild meerkats (Suricata suricatta) through ontogenetic patterns in offspring reproductive hormones (androstenedione, A4; T; estradiol, E2), IGF-1, growth from pup emergence at 1 month to puberty at 1 year, and survivorship. In this non-model, cooperative breeder, adult females naturally, albeit differentially by status, express exceptionally high androgen concentrations, particularly during pregnancy. The early growth of daughters predicts future breeding status and reproductive success. We examine effects of normative and experimentally induced variation in maternal androgens by comparing the male and female offspring of dominant control (DC or high-T), subordinate control (SC or lower-T), and dominant treated (DT or blocked-T) dams, the latter having experienced antiandrogen treatment in late gestation. The offspring showed sex differences in absolute T and IGF-1 concentrations, developmental rates of A4 and E2 expression, and survivorship -effects that were sometimes socially or environmentally modulated. Atypical for mammals were the early male bias in T that disappeared by puberty, the absence of sex differences in A4 and E2, and the female bias in IGF-1. Food availability was linked to steroid concentrations in females and to IGF-1, potentially growth, and survival in both sexes. Maternal treatment significantly affected rates of T, E2, and IGF-1 expression, and weight, with marginal effects on survivorship; offspring of DT dams showed peak IGF-1 concentrations and the best survivorship. Maternal effects impact offspring development in meerkats, with associated trade-offs: Whereas prenatal androgens modify postnatal reproductive and somatic physiology, benefits associated with enhanced competitiveness in DC lineages may have initial costs of reduced IGF-1, delay in weight gain, and decreased survivorship. These novel data further confirm the different evolutionary and mechanistic pathways to cooperative breeding and call for greater consideration of natural endocrine variation in both sexes.